Mukbang mania: exploring attitudes and parasocial relationships among viewers - Hermina, Nurul; Setiadi, Iwan Kresna; Fadhlurrahmah, Sitti Nur Azmi (Jurnal Siasat Bisnis, 2025)
Purpose – This study aims to examine how the motivation to watch mukbang influences attitudes towards watching content and para-social relationships, which ultimately result in the intention to watch content and purchase intention using the stimulus-organism-response (S-O-R) framework.Design/methodology/approach – Using a quantitative approach, this study was conducted on 400 respondents of generation Z and millennials selected using the purposive sampling method. The data obtained were processed using structural equation modeling with SmartPLS 3.0 software.Findings – The findings of this study indicate that visual appeal, auditory elements, and content variety can influence attitude toward mukbang content, while frequency of interaction, content relatability, and engagement level influence parasocial relationships. Furthermore, attitude toward mukbang content and parasocial relationships can lead to intention to watch mukbang, which also influences purchase intention.Research limitations/implications – This study only used samples from generation Z and millennials in Indonesia, which may not be fully representative of the wider population. Future studies could explore different demographic groups or add other variables such as emotional motivation.Practical implications – The results of this study provide insights for content creators and marketers to pay more attention to visual, auditory, and content variation elements in mukbang to increase audience engagement. Strengthening parasocial relationships can also be used as a marketing strategy to increase purchase intentions.Originality/value – This study highlights the influence of viewing motivation on attitudes and parasocial relationships in the context of mukbang, which is still rarely explored in the literature. This study contributes to the understanding of digital consumer behavior, especially among generation Z and millennials.